A Replication Study for the Association of rs11190870 With Curve Severity in Adolescent Idiopathic Scoliosis in Japanese. Issue 10 (15th May 2018) - Takahashi, Yohei; Kou, Ikuyo; Ogura, Yoji; Miyake, Atsushi; Takeda, Kazuki; Nakajima, Masahiro; Minami, Shohei; Kawakami, Noriaki; Uno, Koki; Ito, Manabu; Yonezawa, Ikuho; Kaito, Takashi; et al.
Abstract : Study Design: Case-only study. Objective: The aim of this study was to confirm the association of rs11190870 with adolescent idiopathic scoliosis (AIS) severity in Japanese patients with AIS. Summary of Background Data: Although the association of rs11190870 with AIS susceptibility is replicated in multiple ethnics, the association of rs11190870 with curve severity is controversial. Since the previous studies are of small, we performed a replication study using far larger number of patients than previous studies. Methods: A total of 1860 Japanese patients with AIS who had reached skeletal maturity or undergone surgical fusion were included in the study. We evaluated the association between rs11190870 and AIS progression for the entire group, and then for patients grouped according to a severe curve (a Cobb angle of ≥40°) or mild curve (a Cobb angle <30°). Because braces could affect the results of the present study, patients in the mild-curve group were divided according to whether or not they had worn a brace. We then evaluated associations between rs11190870 genotype and curve severity in these groups. Results: The mean Cobb angles were 54.8° ± 12.1° in the severe-curve group and 24.4° ± 4.0° in the mild-curve group. The difference in rs11190870 risk-allele frequency between the severe- and mild-curve groups was evaluated. No significant differences were observed. We then examined the association of rs11190870 risk-allele frequency between patients in the mild- and severe-curve groups using the χ 2 test for three models, and found a marginal association between rs11190870 and curve severity in the dominant model ( P = 0.035, odds ratio = 1.51). Conclusion: We found no association between rs11190870 and curve severity using the criteria of previous study. However, we found a marginal association between rs11190870 and curve severity. Large-scale replication studies that consider skeletal maturity and brace history, including replication studies in other ethnic groups, would be helpful for clarifying the association. Level of Evidence: 4